Responsibilities of Land Deed Officials in Making Sale and Purchase Deeds Without the Approval of the Rights Holder on the Land Certificate - Zumzumi, Aida Nuriy (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Legal certainty is a key pillar of law enforcement in Indonesia, especially in resolving land ownership disputes. This study examines the Marabahan District Court Decision, which reflects the complexity of resolving disputes related to updating ownership certificate data after a legitimate sale and purchase transaction. This conflict involved the buyer, seller, and the National Land Agency (BPN) due to the failure to update ownership data. The absence of the defendant further exacerbated the legal uncertainty faced by the plaintiff. The court's decision to grant the plaintiff's lawsuit demonstrates the importance of legal and administrative reforms in the land registration system in Indonesia. This study provides a comprehensive overview of the role of legal procedures, public awareness, and institutional responsibility in achieving legal certainty in resolving land disputes. This study discusses the role and responsibilities of PPAT in ensuring the validity of the land sale and purchase process, especially in cases where the land certificate is still registered in the name of another and the legal implications for PPAT and the parties involved if there is negligence in recording the transfer of land certificates, as regulated in Indonesian laws and regulations related to land. This study uses a normative juridical method, a conceptual approach through a doctrinal view, a data collection method using literature studies and the research specifications used are analytical perspective techniques. And the data analysis method uses qualitative analysis.